STRUCTURAL AND MECHANICAL PROPERTIES OF THE CUTTING - Sokhibov Ibodullo Adizmurodovich; Sayliev Ismat Ismatovich (American Journals Publishing, 2022)
The article covers the properties of capillary-porous multiphase food half-finished products processed by the method of sliding cutting, as well as research of cutting objects using various rheological models.
Keywords: rheological model, blade, quasi-static mode, plastic deformation, macromolecule, micro-teeth, spongy protein framework